USING OF INTERACTIVE TEACHING METHODS IN THE PROCESS OF SELF- EDUCATION OF FUTURE TEACHERS - Inogamova, Dilfuza; Rustamova, Nodira (International Journal of Psychosocial Rehabilitation, 2020)
This article is written in order to substantiate the theoretical foundations of the use of interactive teaching methods in the process of self-education of future teachers. The following tasks are defined in the article: how to identify the structure and content of self-education of university students of pedagogical specialties; to reveal the possibilities of implementing interactive teaching methods in the self-education of future teachers; to develop a model of the process of self-education of future teachers in interactive learning; substantiate the ef ectiveness of the implementation of interactive teaching methods in the self-education of students of a pedagogical university. Also, conclusions and recommendations on this issue have been developed.